Clinical outcomes of MII oocytes with refractile bodies in patients undergoing ICSI and single frozen embryo transfer - Hiromi Takahashi; Junko Otsuki; Michio Yamamoto; Hiroe Saito; Rei Hirata; Toshihiro Habara; Nobuyoshi Hayashi (Reproductive Medicine and Biology, 2020)
Abstract Purpose This study aimed to analyze whether the presence of refractile bodies (RFs) negatively affects fertilization, embryo development, and/or implantation rates following intracytoplasmic sperm injection (ICSI). Methods This retrospective embryo cohort study involved a total of 272 patients undergoing ICSI treatment of blastocyst cryopreservation. Results In the study, no significant differences were found regarding 2PN formation rates between RF(+) (76.5%) and RF(−) oocytes (77.2%). However, the blastocyst formation rate on Day 5 in RF(+) oocytes was 45.8%, which was significantly lower than that of 52.2% in RF(−) oocytes (aOR 0.74, 95% CI 0.59‐0.93, P = .011). Implantation rates were also significantly lower in RF(+) oocytes (24.2%) as compared to RF(−) oocytes (42.2%) (aOR 0.46, 95% CI 0.26‐0.78, P = .005). Furthermore, the implantation rate of RF(+) oocytes (28.6%), when high‐quality blastocysts were transferred, was significantly lower than that of RF(−) oocytes (46.1%) (aOR 0.50, 95% CI 0.25‐0.96, P = .043). Conclusion Our results suggest that oocytes with the presence of RFs have a lower potential for blastocyst development. Even when they develop into high‐quality blastocysts, the chances of implantation are reduced.